Eksplorasi dan uji aktivitas antimikroba jamur endofit dari daun mangga kasturi (Mangifera casturi Kosterm.) terhadap Escherichia coli ATCC 25922, Candida albicans ATCC 10231 dan Staphylococcus aureus ATCC 25923 - Razak, Indira Rahmana; Martina, Atria (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANA, 2024)
The kasturi mango ( Mangifera casturi Kosterm.) is  categorized as an endangered plant in situ or Extinct in the Wild according to the IUCN Red List Categories, This also puts under threat the existence of endophytic fungi in these plants. This study aimed to isolate, characterize, and assay the antimicrobial activity of endophytic fungi from mango leaves toward   Escherichia coli , Staphylococcus aureus , and Candida albicans . The fungi were screened for antimicrobial activity using the agar diffusion method. Antimicrobial activity was assessed by measuring the inhibition zone produced by endophytes against the pathogenic microbes. A total of 23 isolates belonging to 4 genera and 1 group of fungi were successfully isolated.  Fungi belonging to the genus Aspergillus with a total of 13 isolates were dominant compared to Penicillium , Cladosporium , Syncephalastrum , and the Mycelia sterilia group. All isolates were able to inhibit the growth of S. aureus with the inhibition zone ranging from 13-23 mm, which is higher than Ampicillin 10 µg/ml. The endophytic fungi obtained were more effective at inhibiting the growth of S. aureus than E. coli , but lacked the ability to inhibit C. albicans .